Systematic Literature Review and Multiple Case Study: Cooperative Defaults and Covid-19 - Zuhri Ruslan (Formosa Journal of Sustainable Research, 2023)
The phenomenon of cooperatives failing to pay up to trillions of rupiah and killing tens of thousands of people is rife in Indonesia. This study aims to investigate and confirm the causes of cooperative defaults, how the process of default occurs and whether it has anything to do with the Covid-19 pandemic. The method used is Systematic Literature Review and Multiple Case Study. The results of the study explain the factors that make cooperatives fail to pay. External factors, namely the member's business went bankrupt and there was no member's good faith in returning the loan funds. Internal factors are risky borrower profiles, yields that are too high, lack of monitoring, collection efforts, and management factors. Covid-19 also had an effect because it made member businesses bankrupt or lost, and made the number of borrowers from cooperatives increase significantly